THE EFFECT OF THE USE OF SIA AND INFORMATION TECHNOLOGY ON EMPLOYEE PERFORMANCE AT PT. CAPELLA PATRIA UTAMA - Vincent Lung; Tina Miniawati (ZILLZELL MEDIA PRIMA, 2025)
This study examines the impact of accounting information systems (AIS) and information technology (IT) on employee performance at PT. Capella Patria Utama. Using a quantitative approach, data were collected through questionnaires involving all 34 employees as respondents. The total sampling method was used to ensure comprehensive analysis. Findings show that AIS and IT implementation significantly enhance work efficiency, accuracy, and decision-making. Employees experience reduced errors in financial reporting and improved productivity. The study highlights the need for continuous system upgrades, employee training, and IT support to maximize these benefits. These results provide insights for management to optimize AIS and IT use for better performance. Future research could explore long-term effects and broader organizational impacts of IT integration.